Thermal characteristic of double-row cylindrical roller bearing of high-speed train using analytical solution and finite element analysis. Issue 1 (July 2021) - Zhang, Kai; Hu, Hanping; Liu, Xiaojie
Abstract: The complicated thermal characteristics critically affect the reliability of double-row cylindrical roller bearing (DCRB) in the high-speed railway, which will cause the deformation and vibration and severely lead to bearing failure. Thus, research on the heat distribution and steady temperature field is essential for DCRB. In this paper, the Green's function was established and programed with MATLAB under certain boundary conditions to verify the temperature field of DCRB. It computes fast than the finite element analysis (FEA), According to the simulation of ANSYS, temperature in outer ring is higher than inner ring and it is the maximum in roller, while the rib reduces the temperature in bearing and temperature near rib is larger, which result in asymmetry in raceway. All these results are consistent with the accrual working. This paper provided a heat portion equation between the rollers and the raceway and calculated more accurate and comprehensive than other equation. All results in this paper made sure the more exact temperature field in the DCRB with more convenient calculation and verification.